Indole-3-Acetic Acid Controls Cambial Growth in Scots Pine by Positional Signaling - Uggla, Claes (American Society of Plant Physiologists, 1998)
The vascular cambium produces secondary xylem and phloem in plants and is responsible for wood formation in forest trees. In this study we used a microscale mass-spectrometry technique coupled with cryosectioning to visualize the radial concentration gradient of endogenous indole-3-acetic acid (IAA) across the cambial meristem and the differentiating derivatives in Scots pine (Pinus sylvestris L.) trees that had different rates of cambial growth. This approach allowed us to investigate the relationship between growth rate and the concentration of endogenous IAA in the dividing cells. We also tested the hypothesis that IAA is a positional signal in xylem development (C. Uggla, T. Moritz, G. Sandberg, B. Sundberg [1996] Proc Natl Acad Sci USA 93: 9282–9286). This idea postulates that the width of the radial concentration gradient of IAA regulates the radial number of dividing cells in the cambial meristem, which is an important component for determining cambial growth rate. The relationship between IAA concentration in the dividing cells and growth rate was poor, although the highest IAA concentration was observed in the fastest-growing cambia. The radial width of the IAA concentration gradient showed a strong correlation with cambial growth rate. The results indicate that IAA gives positional information in plants.